Teori Permintaan dan Penawaran dalam Islam: Theory of Demand and Supply in Islam - A. M. Nur Atma Amir (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
In studying economics at a micro level, the discussion is based on individual behavior as economic actors whose role is to determine price levels in the market mechanism process. The market mechanism itself is an interaction that occurs between demand from the consumer side and supply from the producer side. This research tries to study, understand and understand the meaning, factors and laws of supply and demand in Islamic and conventional economics. Apart from that, this research also examines the conceptual differences between Islamic and conventional economics regarding the theory of demand and supply. This research uses qualitative research with a collection method called library research which collects various references that are relevant to the topic of discussion being studied. From the results of this research it can be concluded that demand and supply are two concepts that underlie a very broad range of economic activities. Demand and supply are also the two words most frequently used by economists, both of which are the forces that make a market economy work. Furthermore, the Islamic Economics concept of demand and supply has some similarities with conventional economics, but there are limitations for individuals to behave in accordance with sharia rules. Lastly, Islamic Economics also includes zakat activities which influence supply in economic activities. Islamic economics also provides a solution to balance in price formation.